Accounting Students' Perception of Love of Money, Machiavellian, Religiosity, and Taxation Understanding Towards Tax Evasion - Aji Tri Mulya; Achyani, Fatchan (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study investigates the psychological and ethical determinants of tax evasion by analyzing the effects of Love of Money, Machiavellianism, Religiosity, and Tax Knowledge among undergraduate accounting students. While the use of a quantitative, positivist approach provides a structured method for identifying variable relationships, the study's generalizability is limited due to its narrow sample of 114 students from a single university who may not represent broader taxpayer behavior. Additionally, reliance on self-reported data concerning sensitive topics like tax evasion introduces the risk of response bias, possibly distorting the findings. The complex, culturally embedded nature of constructs such as Love of Money, Machiavellianism, and Religiosity may not be fully captured through standard questionnaires, potentially weakening the validity of the measurements. Although the study finds that Love of Money significantly influences tax evasion, the insignificance of the other variables might stem from measurement limitations rather than a true lack of effect. Future research should incorporate more diverse and representative samples, refine construct operationalization, and consider mixed-method approaches to deepen understanding of the nuanced drivers behind tax evasion behavior.